Effects of Lean Thinking and Emerging Technologies on Breast Cancer Patients' Therapeutic Process During COVID-19 Pandemic: A Case-Control Matched Study - Pellini, Francesca; Di Filippo, Giacomo; Mirandola, Sara; Deguidi, Giulia; Filippi, Elisa; Pollini, Giovanni Paolo (Frontiers in Surgery, 2021)
Aims The advent of the COVID-19 pandemic has led to the sudden disruption of routine medical care, and the subsequent reorganization of hospital structures and therapeutic algorithms, aiming at protecting patients and health professionals. This was inevitably bound to affect our Breast Unit, dilating both pre- and post-operative times. Aim of this study was to evaluate the effect on patients’ flow of organizational and logistic changes (key interventions) based on the lean thinking methodology implemented after COVID-19 outbreak. Methods Clinical and demographic data was retrospectively collected from patients undergoing sentinel lymph node biopsy for breast cancer at the Verona University Hospital from January 2018 to June 2020. Patients enrolled (n=341) were divided into two groups according to date of admission: before (Group A; n=294) and after (Group B; n=47) implementation of key interventions. Each case in Group B was subsequently matched 1:1 with cases from Group A for age, comorbidities and type of surgery (Subgroup A1; N = 47). Pre-admission time (T0) and length of stay (T1) were compared between the three groups. Results Median T0 was 312 hours, whereas median T1 was 24 hours. Patients in Group B had a higher frequency of comorbidities (57.4% vs. 25,2%, p=0.001) and underwent mastectomy more often than patients in Group A (61,7% vs. 36,7%, p=0.001). Both median T0 and T1 were higher in group B than in group A (384h vs. 300h, p=0.001, 48h vs. 24h, p=0.001, respectively). Median T0 and T1 did not significantly differ between Group B and Subgroup A1 (all p>0.05). Conclusions Lean thinking methodologies and new technologies could prove useful in the optimization of preoperative and postoperative times during the current pandemic, minimizing healthcare personnel and patients’ exposure to SARS-CoV-2, and promoting a rational use of limited resources, while complying with oncological principles.